Crisis Communications in a Natural Agricultural Disaster - Erica Irlbeck; Austin Moore (Journal of Applied Communications, 2020)
Wildfires in Texas, Oklahoma, and Kansas in the late 2010s caused seven deaths and catastrophic damage to millions of acres of ranch and farmland. Because of the rural location of these disasters, agricultural communicators were releasing information to media, internal stakeholders, social media, and other agricultural audiences. The purpose of this study was to explore the communications efforts made and subsequent lessons learned from agricultural communicators during the fires. Through a qualitative case study, researchers interviewed 14 agricultural communicators about their experiences in disseminating information about the fires. Most of the findings align with pre-existing literature; however the researchers found that communicators should be prepared to develop a system to communicate about and accept donations, develop a network of organizations that can be supportive in a crisis situation, and let people be the subject of the messaging. The data also indicate that an undergraduate course in crisis communications would be beneficial.
Keywords: Risk & crisis communications; natural disaster; wildfires